Meta‐analysis of intravascular volume expansion strategies to prevent contrast‐associated acute kidney injury following invasive angiography. Issue 6 (13th November 2020) - Michel, Pablo; Amione‐Guerra, Javier; Sheikh, Omar; Jameson, Lauren C.; Bansal, Shweta; Prasad, Anand
Abstract: Objective: To perform a detailed analysis of published data regarding intravascular volume expansion to prevent contrast‐associated acute kidney injury (CA‐AKI) and to determine if an ideal dose of IV fluids can be recommended. Background: Administration of contrast media during invasive angiography is associated with CA‐AKI. Intravascular volume expansion is the most effective intervention to prevent CA‐AKI, yet evidenced based protocols are lacking. Methods: Literature review and meta‐analysis of randomized controlled trials (RCT) of patients receiving IV volume expansion as prophylaxis for CA‐AKI was performed. Normal saline, Lactated Ringer's and sodium bicarbonate were included. The primary outcome was incidence of CA‐AKI. Results: 37 RCTs studying 12, 166 patients were included. Mean age was 67 ± 5 years, 70% of the patients were male. 68% had chronic kidney disease, 41% diabetes, and 30% heart failure. The incidence of CA‐AKI was 9.5% (95% CI: 8–12%). IV expansion versus no volume administration was associated with a lower risk of CA‐AKI (RR:0.62; 95% CI: 0.49–0.77, p < .001). Intensive IV volume expansion was associated with a reduced risk of CA‐AKI(RR: 0.66; 95%CI: 0.52–0.85, p < .01). The intensive IV volume expansion arm received significantly more fluids than the standard protocols: 1, 574(1, 123 – 1, 913) ml versus 849(558–1, 067) ml ( p = .03) without significant difference in the duration of infusion (median of 12 vs. 17 hr, p = .1) or pulmonary edema (1.7% vs 1.3%, p = .7). Conclusions: Despite high variability in protocols used, IV volume expansion is effective in preventing CA‐AKI. Intensive IVF expansion (median 1.6 L over 17 hr) was associated with decreased risk of CA‐AKI.